PENERAPAN METODE PROBLEM POSING DALAM MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD NEGERI 163099 TEBING TINGGI - Bainim Simarmata (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
ABSTRACTThis study aims to improve student learning outcomes of Indonesian subjects through problem posing method. This classroom action research is conducted in 2 cycles with four stages: planning, implementation, observation, reflection. The subjects of this research are fourth grade students of SD Negeri 163099 Tebing Tinggi as many as 34 students. This research uses qualitative decriptive analysis technique. The result of the research shows that the use of problem posing method of Indonesian subjects can improve students 'learning achievement which is marked by students' learning completeness improvement, that is pre cycle (73,52%), cycle I (82,35%), cycle II (94,11%) And declared successful classically 94.11%. Keywords:Problem Posing, Bahasa Indonesia, Learning Outcomes